Synthesis of coagulation factors during long‐term ex situ liver perfusion. Issue 2 (30th July 2021) - Eshmuminov, Dilmurodjon; Hefti, Max; Mueller, Matteo; Schuler, Martin J.; Bautista Borrego, Lucia; Schneider, Marcel André; Koch, Karin; Weisskopf, Miriam; Tibbitt, Mark W.; Dutkowski, Philipp; Rudolf von Rohr, Philipp; Studt, Jan‐Dirk; et al.
Abstract: Robust viability assessment of grafts during normothermic liver perfusion is a prerequisite for organ use. Coagulation parameters are used commonly for liver assessment in patients. However, they are not yet included in viability assessment during ex situ perfusion. In this study, we analysed coagulation parameters during one week ex situ perfusion at 34℃. Eight discarded human livers were perfused with blood‐based, heparinised perfusate for one week; perfusions in a further four livers were terminated on day 4 due to massive ongoing cell death. Coagulation parameters were well below the physiologic range at perfusion start. Physiologic levels were achieved within the first two perfusion days for factor V (68.5 ± 35.5%), factor VII (83.5 ± 26.2%), fibrinogen (2.1 ± 0.4 g/L) and antithrombin (107 ± 26.5%) in the livers perfused for one week. Despite the increased production of coagulation factors, INR was detectable only at 24h of perfusion (2.1 ± 0.3) and prolonged thereafter (INR > 9). The prolongation of INR was related to the high heparin level in the perfusate (anti‐FXa > 3 U/mL). Intriguingly, livers with ongoing massive cell death also disclosed synthesis of factor V and improved INR. In summary, perfused livers were able to produce coagulation factors at a physiological level ex situ. We propose that single coagulation factor analysis is more reliable for assessing the synthetic function of perfused livers as compared to INR when using a heparinised perfusate. Abstract : Discarded livers are able to regain and to maintain their capacity to produce coagulation factors at a physiological level during ex situ machine perfusion for one week. We propose that single coagulation factor analysis is more reliable for assessing the synthetic function of perfused livers prior transplantation compared to INR in a heparinized perfusate.